Cox regression model in survival analysis and examining the residuals - ÇOKER, Elif; YAY, Meral; UYSAL, Ömer (Cerrahpaşa Medical Journal, 2019)
Cox regression model in survival analysis is a method widely used to determine the factors that are effective on survival time. Especially, this method is frequently used in medical research. In this study, research data are taken from 100 women which have just gave a birth. These women have been observed throughout the four months after their delivery. The aim of this process is to ascertain the factors that are effective on lactation time.